Um estudo sobre licenciatura de matemática oferecida na modalidade à distância - Coelho, Flávio de Souza [UNESP] (2015)
The present investigation is sponsored by Fundação de Amparo à Pesquisa do Estado de São Paulo and aims to understand the Licenciate Degree in Mathmatics, which is a Distance Education Course offered by Universidade Federal de Juiz de Fora (UFJF), Minas Gerais, that effectuate occurs within the Update Plan of the University Pedagogical Project. The central question that guides this study proposes, What kind of Distance Education Licenciate Undergraduate Course is this one offered by UFJF? The research is a qualitative one and follows a Phenomenological approach. It is based on the the work of the Edmund Husserl and other phenomenological philosophers. To update a project there must be actions from people who, within the course, perform important roles in different positions; we reached out for these persons and interviewed the course coordinator, a Mathmatics teacher, a teacher in charge of pedagogical matters, and online tutors. The Residential School at Timóteo (MG) has two groups of students; we interviewed the coordinator, the residential tutor, successful students, students who couldn't follow the course regular pace and also the ones who abandoned the course. The following questions were asked, How well did you fit in? and How do you see yourself in the present, past and future activities? After that we transcribed the experience they reported and proceeded its analysis. Based on the inquiry that inquiry and keeping between parenthesis the theoretical framework of Distance Education, we applied phenomenolical reduction, under which we highlighted 739 Units of Meaning (UM) detached from the interviewees narratives. The analyses of the data revealed 50 Nuclear ideas, among these, and following another reduction movement, the phenomenon structure resulted in 5 wide nuclear ideas:1) Curriculum, whose history at Distance Learning Education seems to be an on-going process; 2) Interactional Modes, person-to-person...